EFFECT OF HYBRIDS AND VARYING PLANTING TIME ON GROWTH AND PRODUCTIVITY IN COTTON (GOSSYPIUM HIRSUTUM L.) - PATEL, PINKY; PATEL, J. C; VYAS, K. G. (The Bioscan, 2016)
Productivity of cotton largely depends upon the agronomic production technologies i.e. availability of high yielding improved varieties and hybrids along with optimum sowing time. The result obtained from the field experiment conducted to find out the effect of hybrids and planting time indicated that sowing of cotton seeds on 19th May recorded higher plant height of 21.2, 56.5, 125.9 and 139.9 cm at 30, 60, 90 and 120 DAS, respectively. The number of monopodial branches/plant (2.9 and 3.5) as well as number of sympodial branches/plant (15.0 and 19.9) at 90 and 120 DAS, respectively. Similarly, seed (3396 kg/ha) and stalk (5386 kg/ha) yields of cotton were recorded higher with planting of cotton on 19th May over 30th May, 9th June and 20th June. Further, Bt cotton hybrid exhibited significantly higher values of the growth as well as yields over non-Bt cotton hybrid. In this way, it can be said that the BT cotton hybrid can be sown on 19th May for acquiring maximum production.